EFKETIFITAS SIMPANG BERSINYAL DENGAN SISTEM PENGATURAN DUA FASE PADA JALAN UTAMA DI KOTA PALU (Studi Kasus: Simpang Samratulangi – Sudirman- Cik Ditiro- Haji Hayyun) - Tahir, Anas; Hidayat, Nur (MEKTEK, 2009)
The growth of vehicle every year give impact to traffic intersection performance. The impact of trrafic such as vehicle queueing , traffic jam , rise in delay time and also increase travel time could be caused by traffic control system no effective because the increasing by traffic volumeThis research is conducted in one of Major Street in Palu, namely at Samratulangi – Sudirman Street street is the intersection between Hj. Hayyun – Cik Ditiro Street.In this research, the analyzed by using Manual Kapasitas Jalan Indonesia ( MKJI).From result of analysis by using MKJI , got intersection performance at condition of morning peak reside at service of level C with queue length is equal to 38,73, in the peak day has level of service F with queue length is equal to 65,04 m and afternoon peak with level of service E where the queueing length is 70,07 m. According to value of level of service on the this intersection had shown that traffic control system 2 (two) stage was not effective again